Formaldehyde gas sensor based on nanostructured nickel oxide and the microstructure effects on its response. Issue 1 (January 2016) - Lahem, D.; Lontio, F.R.; Delcorte, A.; Bilteryst, L.; Debliquy, M.
Abstract: NiO nanostructures can be used as a promising material for semiconductor gas sensor to detect formaldehyde at low concentrations (< 1 ppm). Here, the effect of the morphology of the synthesized NiO nanostructures on gas sensing properties is studied and discussed. NiO nanostructures have been synthesized by thermal decomposition of precursors obtained by two different chemical precipitation methods and a sol-gel technique. Thick films of the synthesized NiO nanostructures were deposited by spray coating on alumina substrates fitted with gold interdigitated electrodes and a platinum heater. The gas sensing properties of those NiO films were studied for low concentrations of formaldehyde gas at different working temperatures. A clear difference in response characteristics was observed between the samples prepared by different synthesis routes.